2023
DOI: 10.1371/journal.ppat.1011235
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal neutrophils limit epithelium damage by reducing pathogen assault on intestinal epithelial cells during Salmonella gut infection

Abstract: Recruitment of neutrophils into and across the gut mucosa is a cardinal feature of intestinal inflammation in response to enteric infections. Previous work using the model pathogen Salmonella enterica serovar Typhimurium (S.Tm) established that invasion of intestinal epithelial cells by S.Tm leads to recruitment of neutrophils into the gut lumen, where they can reduce pathogen loads transiently. Notably, a fraction of the pathogen population can survive this defense, re-grow to high density, and continue trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Recruitment of PMNs into and across the gut mucosa is a cardinal feature of intestinal inflammation in response to STm infection and it has been shown that intraluminal PMNs protect the cecal epithelium from STm induced loss of integrity [32]. Here we found that Ecotin was dispensable for PMN recruitment and bacteria amount inside the luminal PMNs were similar upon WT or eco STm infection.…”
Section: Discussionsupporting
confidence: 49%
“…Recruitment of PMNs into and across the gut mucosa is a cardinal feature of intestinal inflammation in response to STm infection and it has been shown that intraluminal PMNs protect the cecal epithelium from STm induced loss of integrity [32]. Here we found that Ecotin was dispensable for PMN recruitment and bacteria amount inside the luminal PMNs were similar upon WT or eco STm infection.…”
Section: Discussionsupporting
confidence: 49%
“…Earlier work using genetically barcoded S . Typhimurium populations had shown that the pathogen population structure in the cecum lumen is established by bacterial growth, influx, efflux, and death and that the Salmonella population structures of the feces resemble those in the cecum [ 46 49 ]. Thus, by analyzing the feces, we could assess the clonal composition of the Salmonella population within the host (that is the cecum lumen) and obtain information about the pathogen population that can be transmitted to new hosts.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in streptomycin pretreated mice, gut inflammation induced by wild-type S . Typhimurium elicits such a pronounced anti-microbial defense that even gut-luminal loads of the inflammation-adapted pathogen transiently decline by 10 to 10,000-fold at day 2 of the infection [ 48 , 49 ] before regrowing to carrying capacity (≈10 9 CFU/g in cecum content or feces). Based on this previous knowledge and our data presented above, we hypothesized that wild-type S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations